2008
DOI: 10.1177/0146167208316689
|View full text |Cite
|
Sign up to set email alerts
|

Political Ideology and Labor Arbitrators' Decision Making in Work–Family Conflict Cases

Abstract: Labor arbitrators were asked to render decisions about grievances brought by employees who had been fired because of problems created by work conflicts with family responsibilities. The study examined the effects of experimentally manipulated grievant attributes (gender, type of work-family conflict) as well as arbitrator attributes (gender, political ideology) on decision making. When employees were depicted as having had child care problems, liberal arbitrators tended to favor female over male grievants, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…This research also points to the powerful role that exposure to a counterstereotypic female exemplar can play undermining the effect of the caregiving cue in eliciting bias. Thus, as confirmed in both this and related research, caregiving scenarios do appear to activate gender stereotyping and result in distinct patterns of gender bias among liberals and conservatives (Biernat & Malin, 2008). Furthermore, this research substantiates the claims made by Biernat and Malin (2008, p. 895) that "though conservatism might generally predict bias in favor of high status groups (and though liberalism might generally predict bias in favor of low-status groups), these patterns may require additional situational triggers…to be expressed.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This research also points to the powerful role that exposure to a counterstereotypic female exemplar can play undermining the effect of the caregiving cue in eliciting bias. Thus, as confirmed in both this and related research, caregiving scenarios do appear to activate gender stereotyping and result in distinct patterns of gender bias among liberals and conservatives (Biernat & Malin, 2008). Furthermore, this research substantiates the claims made by Biernat and Malin (2008, p. 895) that "though conservatism might generally predict bias in favor of high status groups (and though liberalism might generally predict bias in favor of low-status groups), these patterns may require additional situational triggers…to be expressed.…”
Section: Discussionsupporting
confidence: 75%
“…This can serve as a cue to societal gender roles and can activate role congruity-related biases. Indeed, the situational cue of caregiving has been shown to cue different patterns of gender bias among liberal and conservative decision makers (Biernat & Malin, 2008). Biernat and Malin showed that decisions by labor arbitrators regarding employees fired for child care responsibilities are dependent on political ideology such that conservatives favored the male grievant and liberals favored the female grievant.…”
Section: Political Ideologymentioning
confidence: 99%
“…Finally, little is known about how the arbitrators’ attitudes influence their decisions. The results of a small number of prior studies show that arbitrators’ decisions are influenced by their values (Simpson & Martocchio, 1997) and in the case of work-family conflict, their political ideology (Biernat & Malin, 2008), but none that directly link arbitrators’ explicit and implicit gender attitudes to their decisions.…”
Section: The Arbitration Contextmentioning
confidence: 99%
“…Nonprofessional employees comprise 58.8% of our sample. Despite numerous studies concluding that case outcomes are related to occupational differences, this hypothesis was not supported by our data. Case outcomes in terms of a vacatur of an award or a finding in favor of management are positively related to the male sex of the individual as suggested by (Bemmels (1988a, 1988b); Biernat and Malin (2008); and Oswald and Caudill (1991). One problem in this hypothesis is that in the court cases the identity of the individual was not always disclosed.…”
Section: Hypothesesmentioning
confidence: 99%
“…Research showing occupational differences in the arbitration process has included differences in the occupations themselves (Lewin, 1990; Thornicroft, 1989, 1992); differences related to teachers (Clark & Ogata, 2006; Marmo, 1986); IRS agents (Guffey & Helms, 2001); police, law enforcement and firefighters (Johnson, McKenzie, & Crawley, 2007; LaVan & Carley, 1985; LaVan (2007b); LaVan, Katz, & Carley, 1993); and nurses or nurse practitioners (Philipsen, 2008; Turner, 2009). Sex differences may also occur, owing to sex segregation in various occupations (Bemmels (1988a, 1988b); Biernat & Malin, 2008; Oswald & Caudill, 1991).…”
Section: Case Characteristics Related To Case Outcomesmentioning
confidence: 99%